Abdominal and gluteofemoral size and risk of liver cancer: The liver cancer pooling project. Issue 3 (23rd December 2019) - Florio, Andrea A.; Campbell, Peter T.; Zhang, Xuehong; Zeleniuch‐Jacquotte, Anne; Wactawski‐Wende, Jean; Smith‐Warner, Stephanie A.; Sinha, Rashmi; Simon, Tracey G.; Sesso, Howard D.; Schairer, Catherine; Rosenberg, Lynn; Rohan, Thomas E.; et al.
Abstract : Obesity is known to be associated with primary liver cancer (PLC), but the separate effects of excess abdominal and gluteofemoral size are unclear. Thus, we examined the association between waist and hip circumference with risk of PLC overall and by histologic type—hepatocellular carcinoma (HCC) and intrahepatic cholangiocarcinoma (ICC). The Liver Cancer Pooling Project is a consortium of prospective cohort studies that include data from 1, 167, 244 individuals (PLC n = 2, 208, HCC n = 1, 154, ICC n = 335). Multivariable‐adjusted hazard ratios (HRs) and 95% confidence intervals (CI) were estimated using proportional hazards regression. Waist circumference, per 5 cm increase, was associated with an 11% increased PLC risk (HR = 1.11, 95%CI: 1.09–1.14), including when adjusted for hip circumference (HR = 1.12, 95%CI: 1.08–1.17) and also when restricted to individuals in a normal body mass index (BMI) range (18.5 to <25 kg/m 2 ; HR = 1.14, 95%CI: 1.07–1.21). Hip circumference, per 5 cm increase, was associated with a 9% increased PLC risk (HR = 1.09, 95%CI: 1.06–1.12), but no association remained after adjustment for waist circumference (HR = 0.99, 95%CI: 0.94–1.03). HCC and ICC results were similar. These findings suggest that excess abdominal size is associated with an increased risk of liver cancer, even among individuals considered to have a normal BMI. However, excess gluteofemoral size alone confers no increased risk. Our findings extend prior analyses, which found an association between excess adiposity and risk of liver cancer, by disentangling the separate effects of excess abdominal and gluteofemoral size through utilization of both waist and hip circumference measurements. Abstract : What's new? Obesity is known to be associated with primary liver cancer (PLC), but the separate effects of excess abdominal and gluteofemoral size are unclear. In this large, prospective study of PLC overall and by histologic type, the authors found that excess abdominal size is indeed associated with an increased risk of liver cancer, even among individuals considered to have a normal body mass index (BMI). However, people with excess gluteofemoral size alone don't appear to be at increased risk.